Contribution of Soil and Under Storey Carbon Stock in Post Burned Peat Ecosystem as Carbons Storage on Tropical Land - Hamzah Hamzah; Richard RP Napitupulu; Rince Muryunika (Fakultas Kehutanan Universitas Jambi, 2019)
ABSTRACT Forest and peatland fires in the tropics occur on a large scale and cause environmental damage in the lungs of the world. The flames on the burning peat mix with water vapor inside the peat and produce a lot of smoke. The carbon which was previously buried in the soil and stored in stands above it became exposed and united in the life and human environment. It is very important to know the total carbon stocks in peat to see its contribution as carbon sequestration and carbon storage in stabilizing the ecosystem for rehabilitating peatlands in the tropics which are the lungs of the world. This research is limited to the estimation of carbon stocks stored in peat and understorey soil at the rehabilitation site of the Orang Kayo Hitam forest park. The estimation of soil carbon stocks is carried out by measuring the depth of peat at 48 drill points that are systematically placed. The estimation of understorey carbon stocks is carried out by destructive sampling method on a 0,5 x 0,5 meter plot which is repeated 3 times. The results showed that the peat depth varied from 7,2 - > 10 meters. The mean of understorey carbon stocks is 7.74 tons/ha while the mean of soil carbon stocks is 33.183,67 tons/ha.